CONFLICT OF TWO ADULTS BECOMING CAREGIVERS TO A BABY GIRL IN GREG BERLANTI'S LIFE AS WE KNOW IT ROMANTIC COMEDY MOVIE (2010): AN INDIVIDUAL PSYCHOLOGICAL APPROACH - KADIR, DUMA PRADIPTA (2011)
The object of this research is the movie entitled Life As We Know It, by Greg Berlanti. The study investigates how the conflict change life and personality of the major character in Greg Berlanti's Life As We Know It specifically viewed from an individual psychological approach. The research paper belongs to qualitative research. The object of the study is Holly Berenson and Eric Messer in Life As We Know It movie. In this method, the writer uses two data sources. The primary data source is Life As We Know It movie itself, meanwhile the secondary one includes references and materials related to the study picking up from the books or internet. The methods used for collecting data are library research and documentation. The technique of data analysis is descriptive analysis. Based on the analysis, the writer draws some conclusion as follows: first, Greg Berlanti's Life As We Know It tells about the conflict of Holly Berenson and Eric Messer when they becomes caregivers to a baby girl. They do some efforts to overcome their conflict that represents a case study of individual psychology. Second, the major character's personality change after they overcome the conflict, they live together and reach harmonious life.